2004
DOI: 10.1158/0008-5472.can-03-1203
|View full text |Cite
|
Sign up to set email alerts
|

Small Interfering Double-Stranded RNAs as Therapeutic Molecules to Restore Chemosensitivity to Thymidylate Synthase Inhibitor Compounds

Abstract: RNA interference is a post-transcriptional mechanism by which double-stranded RNA specifically silence expression of a corresponding gene. Small interfering double-stranded RNA (siRNA) of 21-23 nucleotides can induce the process of RNA interference. Studies from our laboratory have shown that translation of thymidylate synthase (TS) mRNA is controlled by its own protein end-product TS in a negative autoregulatory manner. Disruption of this process gives rise to increased synthesis of TS and leads to the develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
41
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 32 publications
6
41
0
Order By: Relevance
“…In contrast, Schmitz et al 29 observed only a minor (25-30%) inhibition of proliferation when RKO human colon cancer cells were transiently transfected with siRNA corresponding to the same sequence targeted by the TS965 retrovirus. This might indicate that delivery of the siRNA was more effective in cells stably expressing a gene encoding the siRNA than in cells transiently transfected with the siRNA.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…In contrast, Schmitz et al 29 observed only a minor (25-30%) inhibition of proliferation when RKO human colon cancer cells were transiently transfected with siRNA corresponding to the same sequence targeted by the TS965 retrovirus. This might indicate that delivery of the siRNA was more effective in cells stably expressing a gene encoding the siRNA than in cells transiently transfected with the siRNA.…”
Section: Discussionmentioning
confidence: 89%
“…The siRNA approach has several advantages over the use of chemotherapeutic drugs to reduce TS enzyme activity. For example, the siRNA approach avoids the potential problem of TS overproduction due to drug-induced disruption of TS translational autoregulation 10,29 or enzyme stabilization, 9 since the mRNA itself is destroyed. Furthermore, singlepoint mutations in the siRNA target sequence are not likely to protect the TS mRNA from destruction (Figure 1a), although minor sequence changes can lead to significant levels of resistance to chemotherapeutic drugs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, a control siRNA duplex, GL2, was obtained from Dharmacon. The procedure of transfection of siRNA into cells was as described previously (Schmitz et al, 2004). For ATP7A silencing, human ATP7A siRNA ON-TARGET plus SMART pool (mixed four duplex: CAGAAACGAUAAUACGA UUUU; GAUAAACGCUCCCUAAACAUU; GGUAUUAGCUGUAA AGUCAUU; GCAAAGGAGUCCAUCAUAUUU, Dharmacon) has been used in this study.…”
Section: Silencing Of Ts and Atp7a By Small Interfering Rna Transfectionmentioning
confidence: 99%